Doxorubicin hydrochloride loaded nanotextured films as a novel drug delivery platform for ovarian cancer treatment - ALARÇİN, EMİNE; YAŞAYAN, GÖKÇEN; ORUN, OYA; MEGA TİBER, PINAR (TAYLOR & FRANCIS LTD, 2020)
An approach for cancer treatment is modulation of tumor microenvironment. Based on the role of extracellular matrix in cell modulation, fabrication of textured materials mimicking extracellular matrix could provide novel opportunities such as determining cancer cell behaviour. With this background, in this work, we have fabricated doxorubicin hydrochloride loaded nanotextured films which promote topographical attachment of cancer cells to film surface, and eliminate cells by release of the anti-cancer drug encapsulated within the films. These films are designed to be placed during surgical removal of the tumor with the intent to prevent ovarian cancer recurrence by capturing cancer cell residuals. With this aim, hemispherical protrusion shaped surface textures were acquired using colloidal lithography technique using 280 nm, 210 nm or 99 nm polystyrene particles. Once moulds were formed, nanotextured films were obtained by casting water-in-oil stable polycaprolactone emulsions encapsulating doxorubicin hydrochloride. Films were then characterized, and evaluated as drug delivery systems. According to results, we found that template morphologies were successfully transferred to films by atomic force microscopy studies. Hydrophilic surfaces were formed with contact angle values around 40 degrees.In-vitrodrug release studies indicated that nanotextured films best fit into the Higuchi model, and similar to 30% of the drug is released from the films within 60 days. Cell culture results indicated increases in the attachment and viability of human ovarian cancer cells to nanotextured surfaces, particularly to the film fabricated using 99 nm particles. Our results demonstrated that delivery of anti-cancer drugs by use of nanotextured materials could be efficient in cancer therapy, and may offer new possibilities for cancer treatment.
Keywords: Nanotexture; colloidal lithography; doxorubicin hydrochloride; polycaprolactone; ovarian cancer; TUMOR MICROENVIRONMENT; CELL RESPONSE; NANOTOPOGRAPHY; STATISTICS; RELEASE; TIME; BIOMATERIALS; THICKNESS; ADHESION; ARRAYS